Trends in the swine industry: operations and marketings - Parcell, J.L.; Dhuyvetter, Kevin C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Trends in the size of swine operations in Kansas and the V. S. are toward fewer and larger operations. The number of operations in Kansas and the U.S. continues to decline; however, the number of hogs marketed has increased because of an increase in operation size. Kansas producers have increased operation size at a slower rate compared to U.S. producers. Kansas ranks tenth nationally in hogs marketed. A migration of swine production from eastern, central, and northern Kansas to southwest Kansas has occurred in the past 5 years.
Keywords: Swine; Swine operations; Hog marketings; Trends